The Effect of the Length of Cuttings and the Dose of Rabbit Manure on the Growth and Yield of Purple Sweet Potato (Ipomoea Batatas L. Poiret) - Made Suarta; Ketut Agung Sudewa; I Putu Adi Masaji (Agriwar Journal, 2021)
This study aims to determine the effect of the length of cuttings and the dose of rabbit manure on the growth and yield of purple sweet potato, which was carried out in Banjar Uma Kepuh, Buduk Village, Mengwi District, Badung Regency, Bali Province. The implementation time of the research starts from March - July 2021. The design used in this experimental design is a Randomized Block Design (RDB). The first factor was the length of the cuttings: S1 (40 cm), S2 (50 cm), and S3 (60 cm). The second factor was the dose of rabbit manure K0 (without fertilizer), K1 (5 tons/ha), and K2 (10 tons/ha). Observation variables included stem length per plant, number of shoots per plant, number of leaves per plant, tuber diameter per plant, number of tubers per plant, fresh weight of tuber per plant, fresh weight of tuber per plant, the weight of oven tuber per plant, dry weight number of ovens per plant and harvest index. The results showed that the length of the cuttings had a significant to a very significant effect on the observed variables except for the largest tuber diameter per plant, tuber fresh weight per plant, and tuber fresh weight per plant had no significant effect. The results of this study indicate that the best cutting length is 50 cm. The dose treatment of rabbit manure had a significant to a very significant effect on the observed variables except for the number of tubers per plant, which had no significant effect. The kind of dose of rabbit manure that gives the best economic results is without rabbit manure. There was an interaction between the length of cuttings and the dose of rabbit manure which had a very significant effect on the observed variables except for the number of shoots per plant, the number of tubers per plant, and fresh weight per plant. The best combination obtained in this study was treatment with cuttings length of 50cm and without a dose of rabbit manure.